2008
DOI: 10.7903/cmr.517
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Upward Influence Strategies on the Communication Media Selection

Abstract: In asymmetric interpersonal relationships between a manager and the employee, the media selection behavior under formal or informal context is likely influenced by the upward influence strategy of an employee. According to increasing the usage of online communication media such as electronic mail, internet bulletin board, and chat software and so forth, the styles of media selection have been also changed. Although many studies related to the usage of offline-oriented communication methodologies in organizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Dealing specifically with the impact of the communication media, Barry and Bateman [6] suggested that influence tactics and media usage, were influenced by the hierarchical position of the individuals and the direction of the intention of influence (upwards, downwards or horizontal). The work of Cho et al [7] is the only one that has specifically focused on upward influence tactics. They found that personal preference in terms of influence tactics, and interpersonal relationship between agent and target, affected media choice.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Dealing specifically with the impact of the communication media, Barry and Bateman [6] suggested that influence tactics and media usage, were influenced by the hierarchical position of the individuals and the direction of the intention of influence (upwards, downwards or horizontal). The work of Cho et al [7] is the only one that has specifically focused on upward influence tactics. They found that personal preference in terms of influence tactics, and interpersonal relationship between agent and target, affected media choice.…”
Section: Theoretical Backgroundmentioning
confidence: 99%